Ketogenic Diet and Hormonal Therapy in Prevention of Evolution of West Syndrome to Lennox-Gastaut - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Medical records of 98 patients diagnosed with West syndrome and monitored at Sanggye Paik Hospital, Seoul, Korea, for at least 3 years were retrospectively reviewed to assess etiology, age at onset, value of various therapies, and the rate of evolution from West syndrome to Lennox-Gastaut syndrome.